Millennial’ Preferences of Communication Systems in the Workplace - Human, Erin (The IIE, 2020)
Millennials have the power to influence organisations as they will soon become the dominant generation in the workforce. Making sure this generational cohort is empowered, engaged and productive is critical, specifically for a country like South Africa who experience a tough economic climate, worsened by the COVID-19 pandemic. Millennials have been branded lazy, entitled, and self-centred, and it is this sentiment which provides the basis for the research. The research aimed to answer what Millennials’ preferences of communication systems are, and whether they are stifled by traditional communications systems and why. The research study utilised the Interpretivist paradigm, encompassing the Axiological and Ontological perspectives, encouraging a qualitative research approach. The qualitative data collected was done by means of an online survey and in-depth interviews. The research yielded 45 respondents for the online survey and 1 interview participant. The data was then analysed using open coding and thematic content analysis. The researcher found that respondents place high value in communication, but do not feel engaged or empowered by traditional communication systems which are still in place. The generational gap within in the workforce was highlighted, with a strong sentiment that they are being held back by leaders who are not adaptive or agile. Based on the results of the data, the findings suggest the feasibility for further research, and the researcher has made several recommendations collected and presented them to the reader.
Keywords: Digital communication; Generation Y; Net generation; COVID-19 pandemic; Traditional communication systems